The building of the chilean literary criticism. Press, culture and power - Nitrihual Valdebenito, Luis; Mayorga Rojel, Alberto Javier; Fierro Bustos, Juan Manuel; Pacheco Pailahual, Stefanie (Estudios sobre el Mensaje Periodístico, 2017)
This paper presents the results of a research project that the authors are developing about the Chilean literary criticism developed in the press. In this context, we propose the revision of the initial development of criticism in the early nineteenth century, and the importance of the press in the formation of the Chilean cultural system. Shown as the critical period begins with the first chilean newspaper, La Aurora de Chile, and is crystallized in the critical work by Andrés Bello.